PERAN TEKNOLOGI WIFI DALAM MENDUKUNG LAYANAN PENELUSURAN INFORMASI PERPUSTAKAAN UNIVERSITAS INDO GLOBAL MANDIRI PALEMBANG - Solehati, Indah; Rohmaniyah, Rohmaniyah (Jurnal Perpustakaan dan Informasi, 2025)
This article discusses the role of WiFi technology in supporting information search services at the Indo Global Mandiri University Library Palembang. The purpose of writing this article is to get an overview of the role of WiFi technology implemented at the Indo Global Mandiri University Library Palembang to facilitate users in accessing literature through literature search services. This article was written using a qualitative approach method with data collection techniques through direct observation in the field, interviews with informants who are librarians of the Indo Global Mandiri University Library Palembang, and documentation. The results of this study can be concluded that WiFi plays a crucial role in improving information accessibility at the Indo Global Mandiri University Library (UIGM), such as access to a number of online journals, e-books, scripts, theses and other scientific works that are digital in nature to support learning and research. But besides that, there are still obstacles in the implementation, namely limited IT experts.